If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 2(x + -4) = -3(x + -8) Reorder the terms: -3x + 2(-4 + x) = -3(x + -8) -3x + (-4 * 2 + x * 2) = -3(x + -8) -3x + (-8 + 2x) = -3(x + -8) Reorder the terms: -8 + -3x + 2x = -3(x + -8) Combine like terms: -3x + 2x = -1x -8 + -1x = -3(x + -8) Reorder the terms: -8 + -1x = -3(-8 + x) -8 + -1x = (-8 * -3 + x * -3) -8 + -1x = (24 + -3x) Solving -8 + -1x = 24 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -8 + -1x + 3x = 24 + -3x + 3x Combine like terms: -1x + 3x = 2x -8 + 2x = 24 + -3x + 3x Combine like terms: -3x + 3x = 0 -8 + 2x = 24 + 0 -8 + 2x = 24 Add '8' to each side of the equation. -8 + 8 + 2x = 24 + 8 Combine like terms: -8 + 8 = 0 0 + 2x = 24 + 8 2x = 24 + 8 Combine like terms: 24 + 8 = 32 2x = 32 Divide each side by '2'. x = 16 Simplifying x = 16
| 858/24 | | X^2-10-20=0 | | .25-2y=13 | | 11b+17-9b=41 | | -25/28*(-21) | | 1/4*7/6 | | 5x=9-16 | | 8x-112=64 | | V=3.14r^2(60-2r) | | 9/28*19/54 | | -2(9n-4)=2(11-8n) | | 2x^(2/3)-x^(1/3)=6 | | -4v+2=2(v+7) | | -8=2(x+6) | | 5x+3y=371 | | w+10=3w-10 | | 4(-5+7a)=26+5a | | 9/28•19/54 | | (14n/3)=8(n-14) | | -25/28•(-21) | | 2X-(5X+9)=8-3X | | 1+6(x-4)=2-8(x-9) | | (x-6)/4=20 | | 4(4+4k)=-32+8k | | -297=4+7(-5v-8) | | 10+2-21=0 | | x-6/4=20 | | ((T^2+3t-8)-(t^2-2t+6))(t-4)=0 | | 7+20x+12x= | | 3-9t=-10t | | 4X+48=8(X+6)-4X | | 252=4(-1-8v) |